Development of Picture Storybooks to Improve Reading Comprehension - Nurul, Annisa; Abbas, Nuraeni (Universitas Negeri Semarang, 2021)
The deficient student reading interest and the lack of learning media in the school lead to a common understanding ofstudents' reading on learning materials. This research aims to develop and test the feasibility and effectiveness of picturebook media. This research uses research and development with Sugiyono model. The results showed that the feasibilityof material in picture storybooks was rated feasible (81.81%), while media eligibility in picture storybooks was ratedhighly feasible (91.67%). Based on the average difference through the t-test showed that sig (2-tailed) 0.000 0.05, itwas concluded that the average value between pretest and posttest had significant changes and an average increase throughthe calculation of n-gain of 0.621 with a moderate category.Keywords: picture storybooks; reading ability; reading comprehension